A Based-Bee Algorithm Approach for the Multi-Mode Project Scheduling Problem - Niño, Karen; Peña, Jorge (Procedia manufacturing, 2019)
Solving the resource constrained project scheduling problem (RCPSP) through exact and approximate approaches has an important role in real life to the extent that they support making decisions regards to the allocation of resources and activities scheduling. Accordingly, this work presents a Based-Bee algorithm for the RCPSP under multi-mode conditions in order to minimize the total completion time of the project. The complexity of this problem lies mainly in the various modes in which activities can be performed; each mode has variations on the activity duration and resources requirements. The algorithm uses random keys strategies to guarantee feasible solutions are always reached. The proposed approach is evaluated with benchmark instances from PSLIB and compared with the recent competitive algorithms reported in literature.